Assessment of reinforced embankment stability over soft soils based on monitoring results. Issue 3 (8th February 2017) - Li, C.; Espinoza, R. D.
Abstract : The stability of a reinforced embankment relies on the contribution of the soil shear strength as well as the reinforcement tensile strength. Typical geotechnical monitoring programmes implemented during construction focus on the deformation of foundation soils without quantifying the contribution of the reinforcement. Therefore, the collected information does not provide a direct indication of the stability of the reinforced embankment. This paper presents a semi-empirical method to assess the stability during construction of a reinforced embankment constructed over soft ground. A finite-element model was used to analyse the stability of a 20 m high, 2.4 km long reinforced embankment being constructed over soft dredge/alluvium. The finite-element model was used to evaluate the process of how the reinforcement tensile strength and foundation shear strength are mobilised during the course of construction and to study the potential correlations between the degree of mobilisation for soil shear strength and monitoring results. The analyses show that the ratio of maximum lateral displacement ( δ ) to embankment settlement ( S ) can be used to assess the degree of shear strength mobilised in the foundation soils.